Does Inclusion Work? Teacher Verification of Proof of Impact - Holmes, Sherwin D.; Barclay, Joyce W.; Dupuis, Bonnie; Lewis, Valerie K.; Platt, Morgan; Shaha, Steven H. (Journal of the American Academy of Special Education Professionals, 2006)
Despite laws, research and public pressures, many educators remain unconverted regarding the beneficial impacts Inclusion can have. This research presents data from the teachers’ perspective that further validates the favorable impacts of Inclusion for students with disabilities. Furthermore, the studies provide significant data regarding the beneficial academic and attitudinal impacts for the general education classmates, substantiation generally missing within the literature. Finally, a correlation between the level of implementation and the favorability of teacher attitudes, indicating that educator perceptions of Inclusion effectiveness improve as their experience with it increases.